Mempersoalkan Hukum Perkawinan Beda Agama di Indonesia melalui Perspektif Hak Asasi Manusia - Alfian, Andi (DIKTUM: Jurnal Syariah dan Hukum, 2024)
This research problematizes the law of interfaith marriage in Indonesia and its application. By presenting some cases of interfaith marriages that occurred during 2022, through literature searches and media reports, this research shows the tendency of violations of human rights, particularly the right to freedom of religion or belief (FoRB), especially by using the argument of the Marriage Law No. 1, 1974. This study found that marriage law in Indonesia does not provide legal certainty for interfaith marriages, thus allowing certain groups to discriminate against interfaith couples accessing legal marriages. Furthermore, this research argues that one way to make marriage law in Indonesia inclusive is to use the human rights paradigm as the basis for formulating marriage law.